Comparative Study of Different Technique for Medical Image Segmentation: A Survey - Chandale, Abhishek; singh, Divakar (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Image analysis and processing can be done using image segmentation as one of the most critical aspect. Various subsequent processes of image analysis such as object representation object description ,feature measurement get affected as a consequence of segmentation .Other higher level tasks such as object classification also get affected b y segmentation. Due to all above reasons, imagesegmentation is considered as one of the most vital and essential process for providing features like delineration, characterization and visualization of important regions in any medical image. Its is necessary to provide accuracy with less time consumption in medical image segmentation Since manual segmentation is very tedious and time consuming to achieve and medical images are mostly unmanageable to be examined .Hence it is necessary to analysis & review current methods and algorithms accruing and need minimal user interaction in case of medical images. In medical images segmentation, the anatomical structure or region to be examined has to be extracted and delineated so as to improve its visibility. This paper projects importance of decision making process in segmentation of images to extract relevant information.